Child morbidity and mortality by external causes, Distrito Federal, 2015-2019: correlation study (Research, Society and Development, 2021)
Objective: Analyze the correlation between hospitalization and child deaths by external causes and ages, genders, years and period in which they occurred, in Distrito Federal, from 2015 to 2019. Method: Data Correlation of the DATASUS’s Hospital Information and Mortality System by external causes, in the age group from one to nine years. Results: There were 6597 hospitalizations and 147 deaths in the age group and period analyzed. Children from one to four years old had a higher risk of suffering poisoning, suffocation and drowning, while those from five to nine years old had greater risk of suffering transport accidents. Falls constituted most of the hospitalizations; drowning and transport accidents are the biggest causes of death. Boys most likely to suffer any incident. The results were inconclusive about the skin color and analysis of the months didn’t reveal greater risks. Conclusions: Accidents in the two age groups have very different profiles. Most injured children are still male. The danger of drowning, being run over and traffic accidents more often resulting in deaths emphasizes the seriousness of these incidents and, therefore, the greater need for their prevention.